Effects of FeSO4 dosage on nitrogen loss and humification during the composting of cow dung and corn straw. (December 2021) - Mei, Juan; Ji, Kai; Su, Lianghu; Wu, Mengting; Zhou, Xiaojie; Duan, Enshuai
Graphical abstract: Highlights: The effect of FeSO4 on humus substances quality of the compost was analyzed. The protein-like substances content increased during the composting with the addition of FeSO4. FeSO4 inhibited the mineralization of organic matter in compost. FeSO4 could promote the formation of humic acid. A new explanation for the nitrogen loss reduction in compost by FeSO4 was provided. Abstract: The effects of FeSO4 on nitrogen loss and humification were investigated in the composting of cow dung and corn straw. The results showed that all groups met the ripening requirements after 50 days: the temperature was above 50 °C for 12– 17 days; the products had pH values of 6.4–7.6, electrical conductivities of 1.06–1.33 ms·cm −1, NH4 + -N contents of 37.2–61.8 mg kg −1, and the seed germination index of 95%–101%. FeSO4 reduced nitrogen losses by 9.21–15.65% compared to the control group. FeSO4 also improved the compost humification process: the humus substances (HS) contents in the compost product with FeSO4 were 109.82–129.86 g·kg −1, higher than 106.31 g·kg −1 in the control group. The compost product in 3.75% FeSO4 treatment had the highest maturity degree. This study showed that FeSO4 could inhibit the mineralization of organic matter during the composting and accelerate the formation of HS.